A study of colourant uses in illuminated Islamic manuscripts from the Qājār period (1789–1925 C.E), early modern Iran. (October 2021) - Darzi, Maedeh; Stern, Benjamin; Edwards, Howell G.M.; Surtees, Alex; Lamehi Rachti, Mohammad
Highlights: Colourants used in illuminated Qur'ān manuscript was studied. Multi-modal analyses of imaging, elemental and molecular techniques were conducted. Gold, gold-alloy, and brass were identified as gilding composition. Carbon black, ultramarine, Prussian blue, vermillion, and red lead were detected. Raw materials, the nature of colourants and manufacturing technology was theorised. Abstract: The study was undertaken to explore the widespread use of colourants, raw materials and technology of colour production to illuminate Qur'ān manuscripts in the Qājār period, Iran (1789–1925 C.E.). SEM-EDX and µ-Raman spectroscopy were employed as non-invasive/non-destructive complementary techniques. The SEM-BSE images contribute to distinguishing between organic/inorganic origin of colourants and the EDX to identify gilding composition as well as providing a short-list of potential colourants to be confirmed by µ-Raman spectroscopy as a compound-specific technique. The results show the most identified colourants are mineral-based pigment; these include carbon black, ultramarine, Prussian blue, vermillion, and red lead. Brass, pure gold, and a gold-silver alloy were detected as metallic ink/paint as gilding. We hypothesise the red diacritic in S01 have organic nature with an anthraquinone derivative structure, but we were unable to specifically identify it. We also hypothesise the yellow constituents in S02 might contain saffron and lead-containing compound(s) as a thickening agent and/or chemical drier. Our findings were in agreement with information available in Persian and English bibliographical sources on Iranian painting and illuminated manuscripts of the Qājār period. Further analysis by SR-µFTIR, FORS, SERS and HPLC is required to confirm our assumption and to complete colourant identification.